Increased P wave duration and dispersion is associated with catheter-related atrial fibrillation during electrophysiological study - İçen, Yahya Kemal; Sümbül, Hilmi Erdem; Koç, Mevlüt (The European Research Journal, 2019)
Objectives: Catheter-related atrial fibrillation (AF) is a common cause during electrophysiological study (EPS) and prolongs the duration of the procedure.  In our study, we compared P wave duration and dispersion in patients with and without catheter-related atrial fibrillation during EPS.Methods: One hundred forty five patients who had normal EPS findings and who were found to have catheter related atrial fibrillation were included in our study. Electrocardiogram was performed in all patients and the pulse rate, the longest P wave duration (Pmax), the shortest P wave duration (Pmin) and the difference between of those (P wave dispersion: Pdisp) were recorded. EPS was performed in all patients. The patients were divided into two groups as the group 1 (without catheter-related AF) and group 2 (with catheter-related AF).Results: In group 2, EPS time was significantly longer, Pmax and Pdisp were found to be significantly higher, Pmin was found to be significantly lower. Binominal logistic regression analysis revealed that, Pmax (OR: 1.077, 95% CI: 1.043-1.112, p < 0.001), Pmin (OR: 0.889, 95% CI: 0.853-926, p < 0.001) and Pdisp (OR: 1.125, 95% CI: 1.080-1.173, p < 0.001) were all independent predictors for catheter-related AF. In ROC analyses, Pmax cut-off value of 120 ms determined the catheter-related AF with 61% sensitivity and 67% specificity, Pdisp cut-off value of 35 ms determined the catheter-related AF with 80% sensitivity and 71% specificity. Conclusion: Patients with longer Pdisp and Pmax and shorter Pmin may develop catheter-related AF during EPS.